Pengaruh Pendapatan Asli Daerah dan Dana Alokasi Umum terhadap Belanja Modal pada Kabupaten di Jawa Tengah - Nurul Fitriyani; Hilda Kumala Wulandari; Roni; Andi Yulianto; Slamet Bambang Riono (Universitas Muhadi Setiabudi, 2020)
This study aims to determine the impact or influence of local original income (PAD) of the general allocation fund (DAU) and capital expenditure on districts or cities in Central Java Province. This research is a quantitative study by applying secondary data. The research population is a report on the capital expenditure of the district or city government in Central Java province starting from 2019-2020 consisting of 35 regencies/cities. The sample of this study is the capital expenditure report of the local government of Brebes Regency whose APBD realization report is listed in the 2019-2020 APBD realization report and uses purposive sampling. The analysis technique utilized in this study is multiple linear regression with the help of the SPSS application. From the results of the study, it was revealed that the variables of Regional Original Income and General Allocation Fund had a significant positive impact on Capital Expenditure